How Does Perceived Value Impact the Continuance Intention of Co-Branded Streetwear Fashion Goods in Indonesia - Haryo Prabowo Sigit Purwanto (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This paper aims to provide more insight into the streetwear fashion industry, specifically the effects of perceived value towards co-brand equity, co-brand preference, and continuance intention in Indonesia’s streetwear fashion context. This study can serve as a guideline for South East Asian fashion entrepreneurs who plans to use a co-branding strategy in their streetwear business. This research used a purposive random sample of 197 co-branded fashion streetwear consumers was surveyed. Structural Equation Modelling (SEM) was employed to analyze the data through SPSS and SmartPLS software. The result shows that perceived value has significant and positive effects on the continuance intention of co-branded streetwear fashion goods in Indonesia. Co-brand equity and co-brand preference also play a pivotal role in consumers’ continuance intention of co-branded streetwear fashion goods in Indonesia. There are currently a low number of studies exploring the streetwear fashion industry.